2013
DOI: 10.1038/jcbfm.2013.111
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Soluble Epoxide Hydrolase after Cardiac Arrest/Cardiopulmonary Resuscitation Induces a Neuroprotective Phenotype in Activated Microglia and Improves Neuronal Survival

Abstract: Cardiac arrest (CA) causes hippocampal neuronal death that frequently leads to severe loss of memory function in survivors. No specific treatment is available to reduce neuronal death and improve functional outcome. The brain's inflammatory response to ischemia can exacerbate injury and provides a potential treatment target. We hypothesized that microglia are activated by CA and contribute to neuronal loss. We used a mouse model to determine whether pharmacologic inhibition of the proinflammatory microglial en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 52 publications
0
37
0
Order By: Relevance
“…Since inhibition of sEH has been shown to exert potent anti-inflammatory action (Iliff and Alkayed, 2009; Inceoglu et al, 2008; Wang et al, 2013), we quantified the effects of administering TUPS, a small molecule inhibitor of sEH, on TETS-induced seizures and neuroinflammation. Initial experiments focused on determining whether pharmacologic inhibition of sEH was sufficient to protect against TETS-induced tonus and death in the absence of diazepam.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since inhibition of sEH has been shown to exert potent anti-inflammatory action (Iliff and Alkayed, 2009; Inceoglu et al, 2008; Wang et al, 2013), we quantified the effects of administering TUPS, a small molecule inhibitor of sEH, on TETS-induced seizures and neuroinflammation. Initial experiments focused on determining whether pharmacologic inhibition of sEH was sufficient to protect against TETS-induced tonus and death in the absence of diazepam.…”
Section: Resultsmentioning
confidence: 99%
“…This cytosolic enzyme regulates the levels of the epoxy fatty acids, which are bioactive lipid metabolites with anti-inflammatory properties (Iliff and Alkayed, 2009; Inceoglu et al, 2007). The anti-inflammatory effects of epoxy fatty acids and sEHIs have been demonstrated in other models of neuroinflammation, including a mouse model of scrapie (Poli et al , 2013), a mouse model of neurodegeneration following cardiac arrest (Wang et al, 2013), and an in vitro model of amyloid peptide-induced neurotoxicity (Sarkar et al , 2011). We have previously shown that epoxy fatty acids and sEHIs protect against seizures induced by PTZ, and this anticonvulsant activity seems to be mediated, in part, by augmentation of GABAergic signaling (Inceoglu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 In addition, the sEH inhibitor, 4-phenylchalcone oxide (4-PCO) treatment showed significantly reduced neuronal death and improve memory function after cardiac arrest/cardiopulmonary resuscitation. 16 Thus, the effectiveness of EETs and sEH inhibitor for the treatment of central nervous system disorders are expected recently.…”
Section: B S T R a C Tmentioning
confidence: 99%